Análise qualitativa do conteúdo ministrado na disciplina de bioética nas faculdades de odontologia Brasileiras - Gonçalves, Patricia Elaine [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Garbin, Artênio José Isper [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2010)
The study consists on a qualitative analysis of content ministered by Bioethical discipline on Brazilian Dental Schools. Data collect occurred by semi-structured questioners send by e-mail and correspondence. It was used content analysis by categorical analysis technique, according to Bardin. Among 182 Schools, just 57 (31.3%) shows Bioethical Discipline. It was observed that the discipline is ministered on the first or last year of course generally. Principal subjects broached are bioethical dilemma (76.3%) with polemics questions and others actual like abortion, clone, organs transplant, attendance of patient porter of HIV and bioethical historic (65.8%), bioethical fundaments, principles and models (57.9%). 84.4% researched professors, said that bioethical discipline awake interesting on students because it actual and it's face to patient-professional relation too. It was possible to conclude that bioethical discipline treat in its content some actual and polemic themes that influence dental surgeon formation because promote him conscience and responsibility of him role front attention at oral health, and so, this discipline should be implanted, specifically in the first year of all Dentistry graduation courses.
Qualitative analysis of content ministered on bioethical discipline on Brazilian Dental Schools
Keywords: Bioethics; Dentistry; Education; Higher